The effect of skeletal muscle molecular clock on signaling of sportperformance adaptations - Sahar Ghasemipour; Mohammad Faramarzi (Shahid Beheshti University, 2024)
Physiological and behavioral processes of almost all organisms depend on the time of day. In mammals, light enters these processes in the suprachiasmatic nucleus of the hypothalamus, which forms the body's central clock, and synchronizes the body's functions with the 24-hour cycle of light and darkness. In addition to perceptual and cognitive aspects of performance, circadian rhythms affect many aspects related to physiological performance such as muscle strength and flexibility. There is also a strong relationship between physical performance and circadian rhythm of body temperature, with optimal physical performance coinciding with peak body temperature in the early evening. There is a circadian clock or rhythm almost in every cell, and its disturbance leads to many diseases such as type 2 diabetes and metabolic syndrome. Previous findings show that skeletal muscle homeostasis may be disrupted not only due to lack of physica activity and low dietary protein intake, but also due to disruption of circadian rhythm conditions such as continuous night work, shift work, sleep deprivation, and jet lag. In this review study, articles were selected and studied using muscle molecular clock, exercise performance, circadian rhythm, and phenotype keywords from published texts, valid sites and search engines such as Google Scholar and Pubmed. The time of sports activities is very important for performance. Despite the timing of the activity, chrnotype can also be a very effective for performance. According to the reviewed studies, most of the sports performance such as strength, speed, endurance, accuracy, recovery ability, and harmony were better in the evening for athletes in different team and individual disciplines. This superiority in the evening can be attributed to body temperature, hormone release, circadian rhythm, rest and recovery. In some cases, such as swimming, strength and endurance performance was better in the morning.Based on the results of studies presented in this review it could be concluded that biological and physiological rhythms have an effect on individual's physical performance. Despite individual differences and personal preferences in determining training hours, taking into account a specific training time each day and training at the beginning of the day can improve performance. Higher body temperature in the evening, and increasing the level of secretion of hormones such as cortisol and testosterone, could be effective factors for better performance in the evening. However, depending on the type of activity, skill level, gender of the athletes and individual differences, the time to have a better performance can vary. In addition, individual preference to perform activities during the day or night is an important factor in improving performance.